Prevalence of Diabetic Retinopathy (DR) In Rural Areas of Western India - Pavan Humesh Shroff; Kunjan J Patel; Priti R Kapadia; Shivani D Patel (Medsci Publications, 2018)
Background: The prevalence of DR urban and rural parts of India has been evaluated in many studies. But prevalence of DR and its awareness in the rural areas of South Gujarat still remains to be assessed. Objectives The study was conducted to assess the prevalence and awareness of DR amongst Diabetics in rural South Gujarat. Materials & Methods: 180 Diabetic patients in rural areas of South Gujarat were screened for DR between September 2014 and Octo- ber 2015. Ophthalmological Examination including dilated fundus examination was done using Indirect Ophthalmoscope. Patients also answered a set of questionnaire prepared to assess the aware- ness of Diabetes and Diabetic Retinopathy as its complication. Results: The prevalence of DR was found to be 27.78%. Non- Proliferative Diabetic Retinopathy (NPDR) comprised 82% while Proliferative Diabetic Retinopathy (PDR) comprised 18% cases. Duration of Diabetes was found to be significantly associated with DR with prevalence in the age-groups 41-50, 51-60, 61-70 and >70 years being 16.67%, 18.42%, 26.47% and 50% respectively. Aware- ness about Diabetes and DR was extremely low. Conclusion: Present study found high prevalence of DR as com- pared to other studies which were conducted in urban areas of In- dia. Awareness regarding diabetes and its complication was ex- tremely low.